Rapid detection, accumulation and translocation of Coconut cadang-cadang viroid variants in oil palm - Thanarajoo, Sathis Sri (2014)
Coconut cadang-cadang viroid (CCCVd) is the causal agent of the lethal Coconut cadang-cadang disease in the Philippines. CCCVd variants were also found in Malaysian oil palm, but in low concentration and difficult to detect. Palms infected with CCCVd variants were associated with orange spotting (OS) disorder and it was estimated that the average yield from the OS-affected palms was 25-50% lower than the healthy palms. Existing diagnostic methods such as hybridization assay and Reverse transcription polymerase chain reaction (RT-PCR) methods are able to detect CCCVd variants in oil palms; however they are laborious, insensitive and time-consuming. In addition, the relationship between CCCVd sequence variation and viroid accumulation has not been studied. In view of this, the present research was undertaken to produce a simple and rapid detection of CCCVd variants using reverse transcription Loop-mediated isothermal amplification (RT-LAMP) method. Besides that, CCCVd accumulation between two different variants together with movement in inoculated oil palm seedlings was studied using real-time PCR. Simultaneously, the pathogenicity of the two different variants was observed in the inoculated seedlings. CCCVd variants were successfully detected in infected samples as early as 60 min at 60 °C using the primer C2.1. Positive reactions of RT-LAMP showed colour change from orange to green after addition of a fluorescent reagent. The RT-LAMP products generated a laddering pattern on 2% agarose gel electrophoresis with bands of different sizes. The optimal condition for RT-LAMP amplification of CCCVd RNAs from oil palm was at 60 °C for 60 min with 6.0 mM MgSO4, 0.8 M betaine, 2.4 mM dNTPs, 1.6 μM of each inner primer FIP and BIP, 0.4 μM each of outer primer B3 and F3 and 8U Bst DNA polymerase. The sensitivity of both RT-PCR and RT-LAMP was found to be equal. The RT-LAMP primers were specific in detecting CCCVd since they did not amplify other viroids that were used in the specificity test. CCCVd were also detected in some of the random field samples collected. The BLAST program results showed that the amplified product of RT-LAMP was indeed a variant of CCCVd246OP. For viroid accumulation study, two variants of CCCVd (CCCVd246OP and CCCVd293OP) were inoculated into 10 three month old oil palm seedlings each, with 10 control seedlings. A RT-PCR and sequencing was carried out to characterise the CCCVd variants obtained from the inoculated seedlings at different time intervals. CCCVd was detected three months after inoculation in low concentrations. The viroid titre showed that the accumulation of the CCCVd variant in the inoculated seedlings fluctuated without any distinct increasing or decreasing pattern. The results of sequencing analysis showed that CCCVd246OP (Genbank: HQ608513.1) was characterised from seedlings inoculated with CCCVd293OP plasmids. In addition, a 246-nt sequence was also recovered from the symptomatic (OS) seedling with 99% sequence similarity to CCCVd246OP, which confirmed the pathogenicity of this 246-nt CCCVd variant. In viroid movement study, the CCCVd246OP variant was inoculated into 12 seedlings. The seedlings were sampled every three months with three replicates; separating the leaves, stems and roots. CCCVd was detected in the leaves, stems and roots of the oil palm seedlings after three, six, nine and twelve months of inoculation. The quantification showed that CCCVd load varied in different parts of the seedlings, with higher concentrations in the stems and leaves as compared to the roots.